Features of generalized dynamics of quasiparticles in the presence of an external potential field. Part 1. General analysis of the problem - Shmeleva, L.V.; Suprun, A.D. (Functional Materials, 2015)
The influence of the external field (electrostatic) of an arbitrary spatial configuration on the common dynamic properties of the free quasiparticle of type of injecting in the semiconductor or dielectric electron is examined. In the quasi-linear approximation with respect to the external field and in the generalized approximation of flat wave in the phase of wave function the completely agreement of simultaneous quantum description (basic) and a description of the classical type (for the dynamics of quasiparticle) is possible. Correlations, which save determinations of basic dynamic characteristics of quasiparticle the same as they are in the absence of an external field established also.